THE EFFECT OF USING WORD WALL GAME TOWARDS SPEAKING SKILL AT SEVENTH GRADE OF SMPN 10 TEBO - Yulianti; Dodi Widia Nanda; Zumrotun Lutfiah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Word wall is one of the learning media in the form of games that are fun and can make students enthusiastic when learning. This research aims to determine the effect of word wall game towards speaking skill at seventh grade of SMPN 10 TEBO. The method used in this research is an experimental method with a quantitative approach, namely using a non-equivalent control group quasi experimental design. Then the researcher measured the abilities of the experimental class and control class to compare the two groups, who received the same material but had different teaching methods. The data collection instruments for speaking ability were in the form of a pretest and post-test. Data collection analysis using the normality test obtained 0,015>0,05, then the N-Gain score obtained in the experimental class was 54%, which means it can be concluded that the influence of the word wall game is quite effective in leaning to speak. Meanwhile, in the control class 33% was obtained, which means that conventional based teaching was less effective, and it can be concluded that there are differences and influences of the word wall game on students’ speaking abilities in the experimental class and the control class at SMPN 10 TEBO. Keywords: Word Wall Game, Media, Speaking Skill